First nations gambling policy in Canada - Kelley, Robin (Canada West Foundation, 2001)
In recent years, some First Nations across Canada have pursued increased gambling opportunities within their communities. The introduction of on-reserve gambling is seen as an important opportunity to help stimulate economic development, create jobs, and provide revenues to develop much needed infrastructure and social programs. In the long run, some argue that on-reserve gambling would allow First Nations communities to become less dependent on funding from the federal and provincial governments and, in so doing, increase their political and economic sovereignty. However, gambling is not always a economic panacea; the size and scope of the benefits are dependent on a number of factors including the level of market saturation, problem gambling impacts, and the ability to draw gamblers to reserves.